1992
DOI: 10.1007/bf00122064
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface wind stress and drag coefficients: The hexos results

Abstract: Abstract. Turbulent fluxes have been measured in the atmospheric surface layer from a boom extending upwind from the Dutch offshore research platform Meetpost Noordwijk (MPN) during HEXMAX (Humidity Exchange over the Sea Main Experiment) in October-November, 1986. We started out to study eddy flux of water vapour, but discrepancies among simultaneous measurements made with three different anemometers led us to develop methods to correct eddy correlation measurements of wind stress for flow distortion by nearby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
269
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(289 citation statements)
references
References 47 publications
20
269
0
Order By: Relevance
“…The coefficients proposed by Taylor and Yelland [68] yielded implausibly high z 0 when applied to steep young waves originated by a storm over the central Mediterranean Sea and by strong Mistral blowing off-shore of southern France, corresponding to 2.85% of our observations. These extreme z 0 led to absurdly high u * and k w , and thus we imposed a maximum roughness length of 0.01 m. This value roughly matches the maximum expected from the application of alternative formulations for the estimation of z 0 from the wave field [70][71][72][73][74].…”
Section: Transfer Velocitysupporting
confidence: 51%
“…The coefficients proposed by Taylor and Yelland [68] yielded implausibly high z 0 when applied to steep young waves originated by a storm over the central Mediterranean Sea and by strong Mistral blowing off-shore of southern France, corresponding to 2.85% of our observations. These extreme z 0 led to absurdly high u * and k w , and thus we imposed a maximum roughness length of 0.01 m. This value roughly matches the maximum expected from the application of alternative formulations for the estimation of z 0 from the wave field [70][71][72][73][74].…”
Section: Transfer Velocitysupporting
confidence: 51%
“…In WAM the Charnock parameter a c is modified to include waveinduced stress and passed back to the atmospheric model. Moreover, to estimate ac, they implemented not only the Janssen [1989,1991] wave-induced wind stress (WS) mechanism but also the wave age (WA) parameterization for roughness Zo derived by Smith et al [1992] during the HEXOS campaign in the North Sea. Overall, the WA and WS results were similar, for surface variables such as U•o, or significant wave height H s. Relative to the uncoupled simulations, Desjardins et al [2000] and Lalbeharry et al [2000] found that the presence of younger rougher seas in coupled simulations can give a -10% reduction in U•o, particularly near the storm peak.…”
Section: Desjardins Et Al [2000] and Lalbeharry Et Al [2000] Selectedmentioning
confidence: 99%
“…The first level of drag coefficient is the constant value. Going more in details, the sea surface drag coefficient is a function of wind speed, wave state, and atmospheric stability (Monin and Obukhov 1954;Charnock 1955;Large and Pond 1981;Smith et al 1992). However, the parameterizations employed for this coefficient are often only wind-dependent in ocean modeling.…”
Section: Sea Surface Drag Formulations and Comparisonmentioning
confidence: 99%